Winners of the Governor’s Prize 2021. Cultural and Educational Center named after St Innokenty in Anga village - Tkacheva, Marina (project baikal, 2022)
The main features of the complex that unites cultural, tourist and religious traditions of the village Anga are described. The new and previously built structures are characterized as a unified system distinguished by the territorial integrity and the landscape zoning. The authors emphasize the importance of the project as a seamless addition to the cultural and historical axis of tourist routes with a starting point from the town of Kachug.
Keywords: Anga village; Cultural and Historical Center named after St. Innokenty; Irkutsk Regional Governor’s Prize; architectural concept; landscape zoning; tourist attraction